Faktor Asupan terhadap Status Gizi Balita Wasting di Wilayah Kerja Puskesmas Sidotopo Wetan Surabaya - Ryka Novitasari; Veni Indrawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Wasting affects health and threatens children potential. Direct factors such as food intake need to be maximized to improve nutritional status. This study aims to determine the differences in energy and macronutrient intake, food parenting, and exclusive breastfeeding history in wasting and non-wasting toddlers in the working area of Sidotopo Wetan Health Center Surabaya. This study is a case control study. Total respondents were 88 toddlers aged 7-60 months, consist 44 wasting toddlers taken with total sampling technique and 44 non-wasting toddlers taken with purposive sampling technique with age and gender matching. Energy intake and macronutrients were obtained by 3x24 hour food recall questionnaire, food parenting patterns obtained from filling out FPSQ (Feeding Practices and Structure Questionnaire) and FPSQ-M (Milk Version) questionnaires, exclusive breastfeeding history obtained through interviews with questionnaires, anthropometric data measured using digital scales and microtoas. Data analysis used independent t-test and Mann Whitney test. The results of this study showed there were significant differences in energy intake (p=0.000), carbohydrates (p=0.023), protein (p=0.000), fat (p=0.000), and exclusive breastfeeding history (p=0.003) and there was no significant difference in food parenting (p=0.632) between wasting and non-wasting toddlers. Parents are expected to pay attention to food intake and provide exclusive breastfeeding.